HUBUNGAN TINGKAT PENGETAHUAN DAN KEPATUHAN DIET PASIEN DENGAN KADAR GULA DARAH SEWAKTU PASIEN DIABETES MELITUS TIPE II DI RSU MUHAMMADIYAH METRO - Hanapertiwi, Sartika; Nurhayati, Aftulesi; Wati, Desti Ambar; Abdullah, Abdullah (Journal Aisyah University, 2024)
A class of metabolic illnesses known as diabetes mellitus (DM) is typified by hyperglycemia, which is quantifiable by blood sugar levels. As the population ages, the prevalence of diabetes rises to 19.9%, or 11.2 million persons between the ages of 65 and 79. With a total of 546 cases, type II diabetes mellitus ranks first among the top 10 conditions at the Muhammadiyah Hospital Metro in 2021. The research objective was to determine the correlation between the knowledge level and dietary compliance with blood sugar levels in type II diabetes mellitus patients at Muhammadiyah Hospital Metro. This research is a quantitative study using a cross-sectional research design with a sample of 56 people consisting of 14 men and 42 women. Purposive sampling was used as a sampling technique. The independent variables in this study were the level of knowledge and dietary compliance, analyzed using a questionnaire on the knowledge level and dietary compliance. Meanwhile, the dependent variable in this study is blood sugar levels at any time. Univariate data is presented in the form of percentage, median, maximum, and minimum. Bivariate analysis used the Mann-Whitney test. The study's frequency distribution reveals that the GDS has a median value of 181 mg/dl, a maximum value of 320 mg/dl, a minimum value of 105 mg/dl, low compliance rates of 14 people (25%), good knowledge levels of 42 people (75%), no diet adherence among 10 people (17.9%), and diet adherence among 46 people (82.1%). According to the study's findings, type 2 diabetes patients at Muhammadiyah Hospital Metro have higher blood sugar levels when their knowledge (p value 0.016) and dietary compliance (p value 0.000) are higher.